“Harmonious” Norms for Global Marketing the Chinese Way - Choukroune, Leïla (Journal of business ethics, 2009)
Whereas the concept of “socialist rule of law” punctuated political discourse in the late 1990s, the idea of a “socialist harmonious society” is today casting a strange light on Chinese legal reform. Is there a Confucian vision of China’s marketing law and practice? To what extent have China’s norms for marketing, mainly intellectual property and advertising law, been challenged by the new government policy toward a harmonious society? In the post World Trade Organization accession period, the theoretical framework of the “socialist harmonious society” has turned law into a disciplinary principle given over to society’s moral construction. If law is seen as an instrument for legitimizing power, it remains implicitly bound primarily to ensure the regime’s durability. Although more and more ordinary citizens and foreign companies are seizing hold of normative tools being put at their disposal, this does not necessarily mean that Chinese law is implemented in a uniform and timely manner throughout China’s territory. China still suffers from a lack of coherence and political will in the drafting of a legal reform that aims mainly at preserving the current fragile political balance. Contradictory forces are indeed at work in this legal construction that is torn between liberal leanings and socialist authoritarianism. Without a deep change in perspective, one can expect only relatively slow progress in protecting the intellectual property rights of the many Chinese and foreign goods and services that can be found on the Chinese market.